2021
DOI: 10.3390/antibiotics10101167
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prevalence Study and Factors Influencing Prescription of WHO Watch Category Antibiotic Ceftriaxone in a Tertiary Care Private Not for Profit Hospital in Uganda

Abstract: Background: Excessive use of ceftriaxone contributes to the emergence and spread of antimicrobial resistance (AMR). In low and middle-income countries, antibiotics are overused but data on consumption are scarcely available. We aimed to determine the prevalence and factors influencing ceftriaxone prescription in a tertiary care private not-for-profit hospital in Uganda. Methods: A cross-sectional study was carried out from October 2019 through May 2020 at Mengo Hospital in Uganda. Patients admitted to the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Inappropriate use of ceftriaxone, which is a third-generation cephalosporin, can accelerate the emergence of AMR of multidrug-resistant organisms, increase treatment cost, and result in avertable adverse drug effects. In Uganda, one study reported 32% inappropriate use of ceftriaxone in nine health facilities while another study reported a high level of ceftriaxone use at a tertiary care, private not-for-profit hospital [ 67 , 68 ]. A possible explanation for the high prevalence of ceftriaxone could be the ease of use (single daily dose) coupled with its wide spectrum coverage, giving the prescriber a sense of broad-spectrum coverage for most infections encountered in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate use of ceftriaxone, which is a third-generation cephalosporin, can accelerate the emergence of AMR of multidrug-resistant organisms, increase treatment cost, and result in avertable adverse drug effects. In Uganda, one study reported 32% inappropriate use of ceftriaxone in nine health facilities while another study reported a high level of ceftriaxone use at a tertiary care, private not-for-profit hospital [ 67 , 68 ]. A possible explanation for the high prevalence of ceftriaxone could be the ease of use (single daily dose) coupled with its wide spectrum coverage, giving the prescriber a sense of broad-spectrum coverage for most infections encountered in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…This high use of antibiotics in healthcare facilities may be due to various diseases that in-patients suffer from and puts pressure on the prescribers to prescribe these drugs for disease prevention and treatment [61] but may promote the emergence of antibiotic-resistance microbes [62]. The [65]. The high prescription rate of ceftriaxone has a high resistance potential and should not be prescribed routinely [65].…”
Section: Discussionmentioning
confidence: 99%
“…The [65]. The high prescription rate of ceftriaxone has a high resistance potential and should not be prescribed routinely [65]. The over-prescription and use of ceftriaxone also highlight the need for antibiotic prescription guidelines at these facilities per national and international guidelines to reduce its irrational use.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for the increase of resistance could be the overuse of ceftriaxone, especially as peri-operative prophylaxis and through prolonged post-operative administration [ 15 , 16 ]. A recent study from Kampala also showed that up to one out of every two patients admitted to medical wards received a prescription of ceftriaxone [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…One explanation for the increase of resistance could be the overuse of ceftriaxone, especially as peri-operative prophylaxis and through prolonged post-operative administration [ 15 , 16 ]. A recent study from Kampala also showed that up to one out of every two patients admitted to medical wards received a prescription of ceftriaxone [ 15 ]. Further gaps can be found in the lack of locally adapted empirical prescribing guidelines for antimicrobials and the low compliance of clinicians with the national clinical guidelines [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%